2011
DOI: 10.2134/agronj2011.0201
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Mapping of the Leaf Area Index in Agricultural Crops

Abstract: Th e leaf area index (LAI), as the ratio of the leaf area to a given unit of land area, is an essential parameter to describe plant productivity and make management decisions. Most methods for estimating the LAI are not suitable for practical agricultural management at the fi eld scale due to delayed availability of data, high costs, or inaccuracy at late growth stages. Th erefore, a new approach for rapid LAI mapping by ground-based laser rangefi nders mounted on a vehicle was evaluated. Two types of laser ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…In-situ studies confirmed the potential of ground-based LIDAR methods, also known as terrestrial laser scanning (TLS), for the assessment of plant parameters in agricultural applications. Previous studies focused on the acquisition of plant height [25], post-harvest growth [26], leaf area index [27], crop density [28,29], nitrogen status [30], or the detection of individual plants [31,32]. Moreover, the potential of TLS for estimating the biomass of small-grain cereals was emphasized [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…In-situ studies confirmed the potential of ground-based LIDAR methods, also known as terrestrial laser scanning (TLS), for the assessment of plant parameters in agricultural applications. Previous studies focused on the acquisition of plant height [25], post-harvest growth [26], leaf area index [27], crop density [28,29], nitrogen status [30], or the detection of individual plants [31,32]. Moreover, the potential of TLS for estimating the biomass of small-grain cereals was emphasized [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Several crops were already investigated with ground-based LIDAR approaches for various purposes like determining plant height (Zhang and Grift, 2012) and estimating biomass (Keightley and Bawden, 2010;Ehlert et al, 2009;, crop density (Hosoi and Omasa, 2009;Saeys et al, 2009), or leaf area index (Gebbers et al, 2011). Furthermore, analysis of the measured intensity values can lead to the detection of single plants of maize (Höfle, 2013) or sugar beet .…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is realistic since HUR1 and HUR2 are continuously measured by soil water content micro-sensors. Up to now, LAI is obtained by reference measurements but automatic methods are in progress (Gebbers et al, 2011;Leemans et al, 2012;Sakamoto et al, 2012). …”
Section: Problem Formulationmentioning
confidence: 99%
“…More recently, methods have been proposed to obtain real-time data processing of LAI. Gebbers et al (2011) developed a rapid mapping of the LAI on the basis of ground-based laser rangefinders mounted on a vehicle. Sakamoto et al (2012) applied a camera-based observation system using vegetation indices for monitoring of seasonal changes in several biophysical parameters of maize such as LAI.…”
Section: Introductionmentioning
confidence: 99%